2015
DOI: 10.5191/jiaee.2015.22104
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Motivations and Barriers Influencing the Decisions of Louisiana State University College of Agriculture Freshmen to Participate in International Experiences

Abstract: Over the past decade, universities in the United States (U.S) have increased time and financial investments put toward internationalizing their curricula, particularly in efforts to increase students' participation in international experiences (IEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 18 publications
7
15
0
Order By: Relevance
“…As mentioned above, this study is part of a larger project seeking to confirm and validate a reliable instrument that administrators and faculty members can use to assess the perceived motivators students may have regarding their decisions to enroll in short-term, study abroad courses or experiences. The findings of this study revealed several moderate and substantial relationships between CASNR students' motivations to enroll in short-term, study abroad courses or experiences prior to being graduated, four of which, including outside effort cost, loss of valued alternatives cost, emotional cost, and task effort cost, were not reported previously in the study abroad literature in agricultural education (Bunch et al, 2013;Bunch et al, 2015;Chang et al, 2013;DanJean et al, 2015;Estes et al, 2016;Place et al, 2004).…”
Section: Discussionsupporting
confidence: 41%
“…As mentioned above, this study is part of a larger project seeking to confirm and validate a reliable instrument that administrators and faculty members can use to assess the perceived motivators students may have regarding their decisions to enroll in short-term, study abroad courses or experiences. The findings of this study revealed several moderate and substantial relationships between CASNR students' motivations to enroll in short-term, study abroad courses or experiences prior to being graduated, four of which, including outside effort cost, loss of valued alternatives cost, emotional cost, and task effort cost, were not reported previously in the study abroad literature in agricultural education (Bunch et al, 2013;Bunch et al, 2015;Chang et al, 2013;DanJean et al, 2015;Estes et al, 2016;Place et al, 2004).…”
Section: Discussionsupporting
confidence: 41%
“…Slightly more than two thirds of the 4-H participants expressed personal interest in participating in an IEP as part of their 4-H program. This is consistent with prior studies conducted with college students (Bunch, Blackburn, Danjean, Stair, & Blanchard, 2015;Danjean et al, 2015), indicating that 4-H youth members, likewise, intend to participate in an IEP. Motivating factors were somewhat important to the 4-H participants when determining whether or not they would participate in an IEP.…”
Section: Discussionsupporting
confidence: 90%
“…Further, they believe that 4-6 weeks is the most appropriate duration and the summer when they would like their student to complete a study abroad experience. These results are similar to research conducted at Louisiana State University that found college of agriculture students believed that 4-6 weeks in the summer of their junior year was the most appropriate time to include a study abroad in their course of study Danjean et al, 2015). Overall, U.S. students do typically study abroad during their junior year, but since 2010, an increasing number of freshman and sophomores have studied abroad (Institute of International Education, 2014).…”
Section: Conclusion and Discussionsupporting
confidence: 75%